Exploration of the Application Rules and Clinical Significance of Acupoints in Acupuncture Treatment of Migraine Based on Data Mining [Letter] - Shen Z; Zhou C; Lin X (Journal of Pain Research)
Zhe Shen,1 Chuanlong Zhou,2 Xianming Lin2 1Zhejiang Chinese Medical University Third Clinical College, Hangzhou, Zhejiang, 310053, People’s Republic of China; 2The Third Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310005, People’s Republic of ChinaCorrespondence: Xianming Lin, The Third Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310005, People’s Republic of China, Email linxianming1966@163.com